Factors Affecting Short-term Mortality in Women With Ovarian, Tubal, or Primary Peritoneal Cancer: Population-Based Cohort Analysis of English National Cancer Registration Data. Issue 1 (1st January 2016) - Barclay, Matthew; Gildea, Carolynn; Poole, Jason; Hirschowitz, Lynn; Menon, Usha; Nordin, Andrew
Abstract : Objective: International studies show lower survival rates in the United Kingdom than other countries with comparable health care systems. We report on factors associated with excess mortality in the first year after diagnosis of primary invasive epithelial ovarian, tubal, and primary peritoneal cancer. Methods: Routinely collected national data were used for patients diagnosed in England in 2008 to 2010. A multivariate Poisson model was used to model excess mortality in 3 periods covering the first year after diagnosis, adjusting for various factors including age at diagnosis, route to diagnosis, tumor stage, tumor morphology, and treatment received. Results: Of 14, 827 women diagnosed as having ovarian cancer, 5296 (36%) died in the first year, with 1673 deaths in the first month after diagnosis. Age older than 70 years, diagnosis after an emergency presentation or by an unknown route, and unspecified or unclassified epithelial morphologies were strongly and independently associated with excess mortality in the first year after diagnosis. Of the 2100 (14%) women who fulfilled all 3 criteria, 1553 (74%) did not receive any treatment and 1774 (85%) died in the first year after diagnosis. In contrast, only 193 (4%) of the 4414 women without any of these characteristics did not receive any treatment, and only 427 (9%) died in the first year after diagnosis. Conclusions: Although our results are based on data from England, they are likely to have implications for cancer care pathways worldwide because most of the identified factors are not specific to the UK health care system. Our results suggest the need to increase symptom awareness, promote timely general practitioner referral, and optimize diagnostic and early treatment pathways within secondary care to increase access to treatment for women with advanced-stage invasive epithelial ovarian, tubal, and primary peritoneal cancer. This process should be pursued alongside continued efforts to develop primary prevention and screening strategies.